Workplace deviant behavior among Jabatan Kerja Raya Melaka’s staff / Siti Aishah Hassan - Hassan, Siti Aishah (2010)
There are main assumptions that burnout syndrome can lead to workplace deviant behavior and negatively affect the organization seriously. Generally the purpose of the study was to discover the relationship between burnout and workplace deviant behavior among staff in Jabatan Kerja Raya Melaka. The burnout covers the emotional exhaustion ,depersonalization and personal accomplishment. While workplace deviant behavior emphasis on the organizational behavior. Based on objectives, the hypotheses were developed and tested using Pearson Correlation, frequency, reliability. The results from hypotheses testing shown that there are relationship between depersonalization with organizational deviance while emotional exhaustion and personal accomplishments do not have relationship with organizational deviance .